Formation of the Kurdish Press: “Kurdistan” Newspaper (Proceedings of Southern Federal University. Philology, 2019)
Kaka Mohammed Omer Kaka (Iraq, Kurdistan)The article is devoted to the first Kurdish national edition – the newspaper “Kurdistan” (1898-1902). The history of its creation and formation is given, first in Egypt, then in Europe. The persecution of the newspaper and its editors by the Ottoman government is described. The role and importance of the newspaper in the formation of national and educational ideas, in the political and cultural unity of the Kurdish people fighting for their independence are emphasized.Key words: Kurdistan newspaper, national identity, Medhat Badrakhan, Ottoman Empire, Suleiman Abdul-HamidDOI 10.23683/1995-0640-2019-2-215-223